POLITENESS STRATEGIES OF FEMALE TEENAGERS IN WILD CHILD MOVIE - KUSUMA WARDANI, RATIH (Language Horizon: Journal of Language Studies, 2014)
POLITENESS STRATEGIES OF FEMALE TEENAGERS IN WILD CHILD MOVIE Ratih Kusuma Wardani English Literature, Faculty of Languages and Arts, Surabaya State University ratihwardani07@gmail.com Lisetyo Ariyanti, S.S., M.Pd. English Department, Faculty of Languages and Arts, Surabaya State University lisetyo.a@yahoo.com Abstrak Bersikap sopan sangatlah penting di kehidupan masyarakat karena kepribadian seseorang dapat terlihat dari cara dia menggunakan strategi kesopanan. Oleh karena itu, mempelajari strategi kesopanan dianggap penting. Skripsi ini berisi tentang strategi kesopanan antar remaja dalam film Wild Child termasuk bagaimana cara Poppy Moore (karakter utama di film) menggunakan strategi kesopanan dan alasan dia menggunakan itu. Tujuan skripsi ini untuk mengetahui cara Poppy Moore menggunakan strategi kesopanan saat berbicara dengan teman-teman remaja perempuannya. Skripsi ini menggunakan pendekatan deskriptif kualitatif dan teori dari Brown dan Levinson tentang strategi kesopanan. Data skripsi ini dikumpulkan melalui proses menonton film, menulis transkripsi dan pengelompokan. Lalu data tersebut dianalisis melaui 3 proses yaitu (1) pengelompokkan data berdasarkan jenis-jenis strategi kesopanan, (2) mendeskripsikan keadaan penggunaannya dan (3) menganalisa alasan penggunaannya. Hasil penelitian menunjukkan bahwa Poppy menggunakan 4 strategi kesopanan yaitu bald on record, positive politeness, negative politeness dan off-record. Bald on record digunakan sebelum dan sesudah berubah kepribadian agar Poppy dapat menarik perhatian teman-teman perempuannya dan agar mereka segera melakukan apa yang diperintahkan Poppy. Poppy menggunakan positive politeness sebelum dan sesudah kepribadiannya berubah untuk menciptakan solidaritas dengan teman-temannya dan untuk menjaga solidaritas tersebut. Tujuan negative politeness digunakan sebelum dan sesudah berubah kepribadian adalah meminimalisir FTA dan untuk menghormati teman-temannya. Terakhir, Poppy menggunakan off-record sebelum kepribadiannya berubah agar aksinya tidak mengganggu teman-temannya. Kata Kunci: politeness, bald on record, positive politeness, negative politeness dan off-record Abstract Being polite is important in people’s life because someone’s personality can be judged and seen through the way he or she constructs politeness strategy. Therefore, learning about politeness strategy is considered as important. This study is about politeness strategies of female teenagers in Wild Child movie including how politeness strategies constructed by Poppy Moore (the main character of the movie) and the reason why she uses those strategies. The purpose of this study is to find out the way female teenager (Poppy Moore) constructs politeness strategies while communicating with her female friends in the movie. In this study, descriptive qualitative approach and Brown and Levinson’s theory about politeness strategies is used. Moreover, the data that have been collected through the process of watching movie, making transcription and classifying are analysed by several process. Those are, (1) the data are classified to the four kinds of politeness strategies, (2) describe the circumstances and (3) analyse the reasons of the using. Finally, the result shows that the way Poppy constructs politeness strategies is by applying bald on record, positive politeness, negative politeness and off-record. Bald on record used before and after her personality changed are to achieve her female friends’ attention and to make her friends directly do what she wants. In using positive politeness before and after her personality changed, Poppy wants to create solidarity to her friends and maintain that solidarity and intimacy. Poppy also wants to minimize the FTA that she uses and respects her friends’ negative face by applying negative politeness. At last, she uses off record strategy before her personality changed because she does not want her act considered as imposing her female friends. Keywords: politeness, bald on record, positive politeness, negative politeness and off-record INTRODUCTION Politeness is a respectful act or manner to indicate regard to other people. In linguistic point of view, politeness is a subject that deals with what kind of language that is appropriate to use in showing regard. Politeness is what we think is appropriate behaviour in particular situations in an attempt to achieve and maintain successful social relationship with others (Lakoff, 1972, p. 910). Actually, being polite is important in people’s life because someone’s personality can be judged and seen through politeness. This study is about politeness strategies between people at the same age specifically female teenagers in Wild Child movie. It is about female teenagers because female are related to politeness strategy (Brown & Levinson, 1987). Moreover, it is focused on teenagers because generally politeness is mostly used to have conversation with older people and between subordinate to superordinate. In this case, this study wants to show that politeness strategy is not only used for young people to older people but also can be used within the conversation among teenagers. Wild Child movie is used in this study. It is a movie directed by Nick Moore, which tells about a young girl named Poppy Moore from America who has to move to England to study in a boarding school. At first, Poppy is a stubborn childish rich girl who likes to hold parties and mostly does whatever she wants to do. Then because she is experiencing an extreme life change since she moved to Abbey Mount (boarding school), she begins to change her personality to be a better person than before. In this case, through Poppy’s personality changes this study wants to analyse whether there are differences in the way she communicates that contains politeness strategies. Moreover, Poppy may have different culture with her friends, she is from America while her friends are from England so she must be used politeness strategies for communicative purposes. It is supported by Lu Yin’s journal (2009, p. 154) that as a universal phenomenon in all societies, politeness is what people of different cultural backgrounds all try to observe for the purpose of increasing communicative competence. In addition, it is thought that analysing politeness strategies is very important because based on the different cultural background there will be a wrong perception that are felt among the speaker and hearer while having conversation. In this case, this study wants to decrease the possibility of having wrong perception itself as what Lestari had said that it is necessary to analyse the politeness strategies in order to avoid or minimize misunderstanding or miscommunication that occurs in cross cultural communication (2009, p. 4). The topic of politeness is not new in linguistics, several years ago there were two previous studies about politeness strategies in English Department of State University of Surabaya. One of the studies is written by Lestari entitled “The Politeness Strategies in the Princess Diaries” which tells about the politeness strategies that are used between granddaughter (Mia Therrnopolis) and grandmother (Queen Clarisse Renaldy). Lestari’s study was written to identify the politeness strategies between two people from different social and cultural background. The study conducted by Lestari was focused to identify the kinds of politeness strategies that are used by Mia and the Queen, the reason why they use these strategies and how the using of these strategies. In data analysis and discussion, bald on record, positive politeness and negative politeness were found as the answers of Lestari’s first research question. On the second and third research question, the reason and the way of using politeness strategies were described in every utterance. Another study is conducted by Munawaroh. The title is “Politeness strategies used by Sister Aloysius in Doubt”. The study was focused only to one female character as the subject that is Sister Aloysius. Munawaroh’s study was aimed to analyse politeness strategies produced by Sister Aloysius in Doubt (a play by John Patrick Stanley) to all the characters in the play. In Munawaroh’s study she used a movie script as the source of data. That study tried to answer research questions about the kind of politeness that is mostly used by Sister Aloysius while communicating with all the characters in the play, why she uses that strategy and the situation of the using itself. In here, Munawaroh found that Sister Aloysius uses positive politeness and negative politeness in her conversations. The strategy that she mostly used in positive politeness is strategy 11 (be optimistic) and the strategy that is mostly used in negative politeness is strategy 3 (be pessimistic). This present study is different from those two previous studies because it uses movie entitled “Wild Child” as the source of data. Moreover, the previous studies show the general view of politeness strategy of young people to older people and vice versa. However, those studies do not show that politeness can also be used among teenagers. So that this study wants to complete the existence of politeness in which it can be used for young to older and also among teenagers specifically female. The research questions of this study are: (1) How politeness strategies are constructed by Poppy Moore to the female teenagers in Wild Child movie? (2) Why does Poppy Moore use politeness strategies? This study is written to find out how politeness strategies constructed by Poppy Moore while having conversations with the female teenagers in Wild Child Movie and to identify why Poppy Moore uses politeness strategies. In this study the focus in only to the conversation between Poppy and her female teenagers’ friends. The significance of this study is to increase the readers’ knowledge and understanding of politeness strategies which are expressed among female teenagers in the movie entitled Wild Child. Moreover, it is hoped that this study could be a basic study for further researchers who are interested in Pragmatic study particularly about politeness strategies. There are four theories that are used in this study. The first theory is about face in Politeness by Brown and Levinson (1987) containing the positive and negative face. Face means ‘sociodynamic valuation’ a lexical hyponym of words meaning prestige; dignity; honour; respect; status (Carr, 1993, p. 90). The second theory is also a theory by Brown and Levinson (1987) named face threatening act. It is some acts intrinsically threaten face (Brown & Levinson, 1987, p. 60). In here, there are two kinds of it, those are acts that threaten speaker’s face and acts that threaten hearer’s face containing positive and negative face. The next theory is politeness strategies including the four kinds of politeness strategies; bald on record, positive politeness, negative politeness and off-record by Brown and Levinson (1987). The last theory is factors influencing the choice of politeness strategy by Holmes (2001) that contains of participants, setting, topic and function. RESEARCH METHOD In this study, the approach that used is descriptive qualitative approach because this study does not use statistic as in the quantitative approach. The emphasis of qualitative approach is on exploring the types of strategy-the qualities-in the data and ascertaining why particular speakers used them in specific contexts with particular people (Wray, Trot, Bloomer, Reay, & Butler, 1998, p. 95). According to the research questions in chapter 1, the questions are about how politeness strategies constructed by Poppy and why she uses these strategies. In this case, the same characteristics between the emphasis of qualitative approach and the research questions can be found. It can be concluded that qualitative approach is the most suitable one to be used in this study. So, that is why this approach is used to conduct this study. The subject of this study is Poppy Moore, one of the female teenagers in the movie. It is because Poppy Moore, a young girl who is moved to England to study in Abbey Mount boarding school is the main character whose personality changed in the movie because of extreme life change that she experienced. The data of this study are utterances that contain politeness strategies produced by Poppy Moore while having conversations with the female teenagers in Wild Child movie. The source of data in this study is Wild Child movie aired in 2008 directed by Nick Moore. Research questions in this study are collected by non-participant observation in which the writer observes the data through taking notes of the object and without making interview or questionnaire. Moreover, the data are collected by 3 steps. Those are: Watch the movie This step consists of repeating the scenes which contain politeness strategies in the conversation of Poppy and the female teenagers over and over. In this step, tools like soft file of the movie, laptop and headset are used. Make transcriptions of the dialogue The transcription is only the dialogue between Poppy and the female teenagers that contain politeness strategies. The tools in this step are book note and pen. Here is the example of transcription: Data 1 Ruby : Not those shoes. They don’t do rain. Poppy : Just take them. Ruby : (smiles and puts on the shoes). Classify the data The classification is whether the data are produced when Poppy’s personality has not changed yet or has already changed. Book note and pen are still used as the tools in this step. In this step, the classification is presented in the form of table. Table 1: classification table Basic Personality Personality Changed Data Utterances Data Utterances 1 Just take them. 16 Come on, quick. The data Analysis are analysed based on the two research questions. Research Question 1 Research question 1 about how politeness strategies constructed by Poppy, describes about the types of politeness strategies, the circumstances of the using and the way poppy expresses those strategies. At first, the data that have been collected are classified to the kinds of politeness strategies, whether bald on record, positive politeness, negative politeness or off-record. The data are classified by relating to the strategies of each kind of politeness strategies. The next step is finding the circumstances of the using. It is related to the situation when the conversation happens. In this case, the situation is related to the act that can threat the hearer’s or speaker’s face. The classifications are displayed in the form of table. In answering this first research question, Brown and Levinson’s theories about politeness strategies and face threatening acts containing the acts that threaten speaker and hearer are used. Research Question 2 To answer the second research question, Poppy’s reason of using politeness strategies is identified by analysing the data and relating to the face of the hearer or speaker, participants, setting, function and situation of the conversation. The reason of every utterances are analysed based on the theory of Brown and Levinson about face in politeness and combines the theory by Holmes about factor influencing the choice of politeness strategy. DATA ANALYSIS AND DISCUSSION Data Analysis In this section, the analysis of research question one and two are displayed integrated on each data. Beside, each data consists of participants including the speaker and hearer, topic, and setting. The first paragraph of analysis is the analysis of research question one, while the second paragraph is the analysis of research question two. Poppy’s Utterances before Her Personality Changed Participants Speaker : Poppy Moore Hearer : Kiki Topic : Poppy criticizes Kiki’s cell phone. Setting : Poppy’s new bedroom in Abbey Kiki : Good luck getting a signal. We only have two spots that work round here. Poppy : Maybe you should try entering the 21st century, Buck Rogers. (Looks at Kiki’s old phone). Mount In her utterance, Poppy uses the word “maybe” that is classified as hedge because it means that word can be true only in certain respects. Poppy’s utterance belongs to negative politeness strategy 2 (question, hedge) because hedges is part of negative politeness. The situation of that conversation is when Poppy’s cell phone is bleeping, because of that Jossie asks what the bleep that is because she does not familiar with that. In that utterance, Jossie shows that she does not know iPhone. Then, Kiki tells that it is an iPhone that is bleeping and says good luck to Poppy in getting signals. After that Poppy gives feedback to Kiki by saying the utterance above. Poppy’s goal in saying that is because she wants to advice Kiki to change her cell phone to a trendy one. Poppy says that to criticise Kiki’s cell phone in soften way. She adds the word “maybe” to indicate that the advice is not a force and because Poppy is aware of Kiki’s negative face. So in this case, it depends to Kiki whether she will change her cell phone or not. The words “entering the 21st century” initiating modern era, which means that by changing her cell phone to the modern one, Kiki can be considered as entering the modern era Poppy’s Utterances after Her Personality Changed Participants Speaker : Poppy Moore Hearer : Poppy’s roommates Topic : Poppy wants to help the roommates to dress fancy. Poppy : I say we dress up fancy. Real fancy. Roommates : (Listens to Poppy). Setting : In the bathroom In the conversation above, Poppy is applying positive politeness strategy 12 (include both speaker and hearer in the activity). It is because she states the word “we” that is categorized as ‘inclusive we’ in this strategy. Inclusive we itself is one of the criteria of this strategy so that is why the utterance stated by Poppy above belongs to positive politeness strategy 12. Poppy says the utterance when she and the roommates are discussing about the school dance on Saturday night. Drippy, one of the roommates utters that only teachers, morons and Harriet that bother to dress fancy. Then Poppy suddenly states that she will help to make them dress up fancy. By uttering that sentence, Poppy wants to maintain her positive face to be liked by her roommates because she wants to help them to look fancy and she wants to gain cooperation of them all to give contribution of effort to dress up fancy. In this case, she uses ‘inclusive we’ to initiate that the roommates are approved as the same member of a group so that is why she needs their cooperativeness. Summary of Data Analysis Table 2: Basic personality table Basic Personality (before Poppy’s personality changed) (stubborn, childish, arrogant) Da ta Utterances Classification Strategy 1 Just take them. Bald On Record (2) FTA oriented Bald On Record Usage 2 Let’s check out their website. Positive Politeness (12) Include S and H in the activity 3 Please, tell me that’s not in the countryside. Negative Politeness (10) Go on record as incurring debt 4 Excuse me. Negative politeness (6) Apologize 5 Oh, wow, communal. Off Record (8) Be ironic 6 Maybe you should try entering the 21st century. Negative Politeness (2) Question, hedge 7 It’s imperative that I make my phone calls. Off Record (1) Give hints 8 How am I supposed to call my therapist? Off Record (10) Use rhetorical questions 9 Not the new season Gucci. No. The Choos. Positive Politeness (4) Use- in group identity markers 10 I might get thirsty. Negative Politeness (2) Question, hedge 11 No wireless. Should have known. Negative Politeness (9) Nominalize 12 Oh look. They’re not out. Bald On Record (1) Non- minimization of Face threat 13 I don’t think I have anything thicker than prosciutto. Negative Politeness (2) Question, hedge 14 Why would you do this for me? Positive politeness (13) Give or ask for reasons 15 Aye, Aye, Captain. Negative politeness (5) Give deference In the table above, the utterances produced before Poppy’s personality changed are displayed. Based on those 15 data, Poppy applies 2 strategies of bald on record, 3 strategies of positive politeness, 5 strategies of negative politeness and 3 strategies of off record. Table 3: After personality changed table Among the 21 data in the after personality changed table, Poppy applies 2 strategies of bald on record, 13 strategies of positive politeness, 3 strategies of negative politeness and none of off-record strategy. Based on the two tables, it is seen that among the 15 strategies of positive politeness, only 11 strategies that are used in this study. In addition, there are only 5 strategies of negative politeness are used in this study instead of 10 strategies. At last, among the 15 strategies of off record, only 3 strategies that are used. Not all the strategies of positive politeness, negative politeness and off record are used in this study because in the movie not all the strategies of politeness strategies are existed and applied. Discussion There are two tables that are displayed above. The first is before Poppy’s personality changed and the second is after her personality changed. It is divided into those two tables because in Wild Child movie Poppy’s personality is changed. At first, she is a problem-maker, always breaks the rules, childish, arrogant and so on then after she adapts with the situation and rules in Abbey Mount, her personality slowly changed. She starts making friends, follows the rules and friendlier. By using those two tables it can also be seen that the way Poppy constructs politeness strategies is different due to the personality changed itself. From the table above it can be seen that before her personality changed, Poppy constructs politeness by applying four kinds of politeness strategies; bald on record, positive politeness, negative politeness, and off record based on the 15 data. She uses bald on record by uttering offer and attention getter to invite hearer to do something and grab their attention. Then, she also applies 3 positive politeness strategies by including speaker and hearer in the activity, stating jargon or slang and asking reason. She applies those because she wants to create solidarity among her and her female friends and also to satisfy their positive face wants. The third strategy that she applies is negative politeness. She applies them by hedging, apologizing, giving deference, nominalizing and going on record incurring debt because she is aware and wants to satisfy her female friends’ negative face since they are still considered as strangers to Poppy and wants to minimize the imposition. Poppy’s aim in using negative politeness is supported Brown and Levinson’s theory that negative politeness is oriented mainly toward partially satisfying (redressing) hearer’s negative face (1987, p. 70). Therefore, Poppy’s reason in using negative politeness because she wants to satisfy her female friends’ negative face has fulfilled the theory above. Moreover, it is stated that showing awareness of another person’s face when that other seems socially distant is often described in terms of respect or deference (Munawaroh, 2010, p. 6). In here it can be said that Poppy’s awareness of her female friends’ negative face is considered as deference. At last, Poppy applies off-record strategy by giving hint, using rhetorical question and being ironic to avoid her from the potential to be imposing or damaging her friends’ face and to hide her intended meaning. Poppy’s aim in doing off record is supported by Brown and Levinson’s theory that by going off record, a speaker can get credit for being tactful, non-coercive; he can run less risk of his act entering the ‘gossip biography’ that others keep of him; he can avoid responsibility for the potentially face-damaging interpretation (1987, p. 71). In here, it is true that doing off-record strategy is aimed to avoid damaging the hearer’s face. In addition, the face threatening acts that she uses before her personality changed are considered as offer, order and apologize. Of the 21 data in the after personality changed table, Poppy constructs politeness by using only 3 politeness strategies after her personality changed. Those are bald on record, positive politeness and negative politeness. There are 5 data of bald on record in the second table. In this case Poppy uses that by applying welcome greeting and urgent imperative. Her reasons are because she wants to make her action direct, clear, and unambiguous and she also wants that hearer directly can do the action by showing the urgency imperatives. Poppy also uses positive politeness in 13 data by promising, joking, avoiding disagreement, including hearer and speaker in the activity, and so on. She applies that because she wants to maintain her positive face to be liked, admired by her female friends by approving them as the same member of a group and claiming common ground with them. It is the same as what Brown and Levinson said that positive politeness is approach based; it ‘anoints’ the face of the addressee by indicating that in some respects, S wants H’s wants (by treating him as a member of an in group, a friend, a person whose wants and personality traits are known and liked) (1987, p. 70). In here, it can be said that Poppy’s act by approving her female friends as the same member of a group is match with the theory of positive politeness above. The last strategy that she uses is negative politeness. In here she applies that strategy by using hedging device, and apologizing. Hickey and Stewart said that a preference for negative rather than positive politeness strategies hitch is played out through a number of linguistic strategies, for example, personal reference, hedging and deictic anchorage (2005, p. 118). So, based on the theory above Poppy’s action by using hedging device is true as the application of negative politeness. Her goal is to show her respects to her female friends’ negative face and not to take full responsibility of her utterances as what Brown and Levinson said that realizations of negative politeness strategies consists in assurances that the speaker recognizes and respects the addressee’s negative face wants and will not interfere with the addressee’s freedom of action (1987, p. 70). In here, the kinds of FTA that she applies are more various rather than before her personality changed. Those are order, criticism, compliment, promises and apologize. Based on the discussion above, it can be concluded that before her personality changed Poppy applies all the four politeness strategies and the dominant is negative politeness because she is still new in her environment and her female friends are considered as strangers who have social distance to her so that is why she wants to minimize the FTA by maintaining her female friends’ negative face. It is as what Brown and Levinson said that the outputs of negative politeness are all forms useful in general for social ’distancing’; they are therefore likely to be used whenever a speaker wants to put a social brake on to the course of his interaction (1987, p. 130). So, it can be concluded that Poppy mostly applies negative politeness before her personality changed for social distancing, supports the theory of Brown and Levinson about the aim of negative politeness. However, after her personality changed, Poppy mostly uses positive politeness because cooperation and intimacy are created strongly between them and they have the same wants. Brown and Levinson said that positive politeness utterances are used as a kind of metaphorical extension of intimacy, to imply common ground or sharing of wants to a limited extent even between strangers who perceive themselves, for the purpose of the interaction, as somehow similar (1987, p. 103). Based on the theory above, it can be said that Poppy supports the theory of Brown and Levinson’s above about the aim of using positive politeness. In addition, Poppy does not use off record strategy because through the intimacy that already created, Poppy does not need to hide her want by giving hints because she can directly utter her wants to her friends. The finding that Poppy generally applies the four kinds of politeness strategies (bald on record, positive politeness, negative politeness and off record) is different with the finding of Lestari’s and Munawaroh’s researches. In Lestari’s research, she found that Mia and Queen Clarisse used bald on record, positive politeness and negative politeness while Munawaroh found that only two strategies (negative politeness and positive politeness) which are used by Sister Aloysius. In here, it can be said that the politeness strategies that are used within the conversation among female teenagers are more various. CONCLUSION AND SUGGESTION Conclusion The conclusion of research question 1 are generally after and before her personality changed, Poppy constructs politeness by applying bald on record, positive politeness, negative politeness and off record. When applying bald on record, Poppy applies two cases of bald on record; cases of non-minimization of the face threat and cases of FTA oriented bald on record usage. In applying positive politeness, she uses positive politeness’ strategies such as notice, attend to hearer (strategy 1), exaggerate (strategy 2), use in group identity markers (strategy 4), avoid disagreement (strategy 6), presuppose/raise/assert common ground (strategy 7), joke (strategy 8), offer; promise (strategy 10), be optimistic (strategy 11), include both S and H in the activity (strategy 12), give or ask for reasons (strategy 13) and give gifts to hearer (strategy 15). Poppy’s ways in applying negative politeness are by using question, hedge (strategy 2), give deference (strategy 5), apologize (strategy 6), nominalize (strategy 9) and go on record as incurring a debt, or as not indebting hearer (strategy 10). For the off-record, she only applies 3 strategies; give hints (strategy 1), be ironic (strategy 8) and use rhetorical question (strategy 10). Moreover, Poppy also does the acts that threaten the hearer’s negative face such as order, promise and compliments, the act that threaten hearer’s positive face such as criticism and act that threaten her own face as the speaker such as apologies. These are the conclusion of research question 2. Poppy’s reason by using bald on record before her personality changed is to achieve her female friends’ attention through the attention getter. Meanwhile after the personality changed, her goal is to make her friends directly do what she wants. In using positive politeness before and after her personality changed, Poppy wants to create solidarity to her friends and maintain that solidarity and intimacy. Poppy also wants to minimize the FTA that she uses and respects her friends’ negative face by applying negative politeness. Finally she uses off record because she does not want her act to be considered as imposing her female friends. At last, through this study it can be concluded that personality changed and differences of culture can influence the way someone constructs politeness. In Poppy’s case, there are differences in the ways she constructs politeness before and after her personality changed since she moved to Abbey Mount boarding school. Suggestion Through this study, it can be seen that politeness is important in people’s daily life. It is used not only to older people but also when communicating with people at the same age. In this case, based on this study it is hoped that people especially female teenagers can know the appropriate kind of politeness strategies that is suitable to be used while communicating to other female teenagers. For the further researchers who interested in politeness strategies, it is hoped that they can find the new idea of application of politeness strategies that happens around society through participant observation or non-participant observation. Moreover, they can also tries to analyse politeness strategies through other sources such as through movie, magazine, novel, short story and other literary works. Moreover, it is also hoped that this study can be a good guidance for further researchers in conducting their researches. REFERENCES Brown, P., & Levinson, S. C. (1987). Politeness Some universals in language usage. New York: Cambridge University Press. Carr, M. (1993). Chinese "Face" in Japanese and English (Part2). ????, 85, 69. Hickey, L., & Stewart, M. (2005). Politeness in Europe. Canada: Multilingual Matters. Holmes, J. (2001). An Introduction to Sociolinguistics (Second ed.). Edinburgh: Longman Group. Lakoff, R. (1972). Language in Context. Linguistic Society of America, 48(4), 927. Lestari, S. F. (2009). Politeness strateegies in the Princess Diaries. under graduate, State University of Surabaya, Surabaya. Munawaroh, L. (2010). Politeness strategies used by sister aloysius in Doubt by John Patrick Shanley. under graduate, State University of Surabaya Surabaya. Wray, A., Trot, K., Bloomer, A., Reay, S., & Butler, C. (1998). Projects in Linguistics : A Practical Guide to Researching Language (third ed.). China: Edward Arnold. Yin, L. (2009). Cultural Differences of Politeness in English and Chinese. Asian Social Science, 5(6), 156.